Value of pre anesthetic consultation on patients owner’s perception about the anesthesiologist (Research, Society and Development, 2022)
Veterinary anesthesiology is an area on the rise within veterinary medicine, so understanding the role of the anesthesiologist is extremely important. The aim of this study is to evaluate the importance of pre-anesthetic consultation in the owner’s perception of the anesthesiologist and his knowledge about this professional as well as his functions and responsibilities. A questionnaire was applied to the owners of the animals attended at HCV/UFPel who would undergo consultation and pre-evaluation anesthetic, the participants were divided into a control group where the questionnaire was applied before any contact with the anesthetist and the test group where the questionnaire was applied after the pre-anesthetic consultation and evaluation of the patient by the anesthesiologist. Altogether, 63 questionnaires were applied, majority answered by women. Both study groups agreed on the need for a pre-anesthetic consultation, as well as both felt safer. Still, the control group showed to have less knowledge about the number of people involved in a surgical procedure, while the test group proved to be less comfortable knowing that the procedure would be performed in a hospital with an anesthesiologist veterinarian. It is concluded that the pre-anesthetic consultation is necessary and provides greater safety to the responsible in relation to the procedure of your pet but it is necessary to improve this in a better way inform and clarify the functions, responsibilities and importance of this professional to the responsible.